Fekete Vonat . Black Train - Schiffer, Pál (Balazs Bela Studio - BBS, 1970)
Every Friday, the "black train" transports workers from Budapest to remote rural areas in Hungary and every Sunday takes them back again to the capital. A film about domestic economic migrants in Hungary.